Enteric Elongation Induced by a Novel Sleeve Device in a Live Roux-en-Y Configuration - Joshua C. Colvin; Collyn C. O’Quin; Hannah R. Meyer; Valerie L. Welch; Giovanni F. Solitro; Jonathan S. Alexander; Donald L. Sorrells (Bioengineering, 2025)
Short bowel syndrome (SBS) is characterized by insufficient intestinal length to support absorption causing malnutrition. The bowel adapts to SBS via intestinal dilation and delayed gastric emptying but still often requires long-term parenteral nutrition. Current surgical options to lengthen the bowel pose significant risks and often provide limited expansion. ‘Distraction enterogenesis’ has been proposed as a technique to induce intestinal lengthening for SBS. The deployment of the intestinal expansion sleeve (IES) device is hypothesized to result in significant intestinal lengthening in vivo. A Roux-en-Y was created in the jejunum of seven rats for isolated IES deployment. The IES was precontracted over a Bucatini noodle and inserted into the isolated roux limb. After 4 weeks of deployment, rats were sacrificed, Roux-en-Y length recorded, and histology analyzed. A paired t-test was performed to compare initial and final roux limb lengths and histopathological tissue remodeling. Intestinal distraction evaluated at 4 weeks post deployment of the IES resulted in a significant 30.2% elongation in roux limb length (43.6 ± 14.4 mm to 56.4 ± 20.8 mm (p = 0.043, n = 7). IES samples showed changes in mucosal and submucosal integrity and bowel wall thickness in response to IES lengthening. In samples with partial mucosal erosion, the basal/regenerative layers of the mucosa were preserved. Distraction enterogenesis with significant intestinal lengthening in vivo has been achieved with the IES device. Histologic changes suggest all bowel functional layers and attributes are maintained through distraction enterogenesis. Future constructs of the IES may benefit from the addition of immunomodulators. Increasing intestinal mass with these devices may complement the treatment paradigm for SBS.